BELAJAR DAN PENGAJARAN MATEMATIKA DI ERA DIGITAL: SYSTEMATIC LITERATURE REVIEW - Rivan Gestiardi; Slamet Arifin; Mardhatillah Mardhatillah; Galuh Tisna Widiana; Devi Wahyu Ertanti (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
Digital transformation in mathematics education has gained tremendous momentum, mainly driven by the COVID-19 pandemic and the emergence of Society 5.0. While digital devices open up exciting possibilities through interactive visualizations and adaptive learning platforms, educators still face significant hurdles in their implementation, from teacher preparation to infrastructure readiness. The purpose of this research is to analyze effective mathematics teaching and learning in the digital era. This research method uses systematic literature review (SLR) by analyzing 16 carefully selected articles from Scopus indexed journals published between 2019 and 2024. Through a comprehensive examination using the PRISMA protocol supplemented with bibliometric analysis, we investigated current trends, effectiveness patterns, and implementation challenges. Our findings shed light on three key insights: mathematics education is naturally evolving beyond simple digitization towards more sophisticated adaptive learning approaches that embrace computational thinking; the success of digital devices is closely linked to thoughtful implementation strategies that respect cultural contexts; and meaningful integration requires careful attention to challenges such as technostress while maintaining pedagogical excellence.